2013
DOI: 10.1016/j.jbiomech.2012.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations in articular cartilage thickness and strain in the human knee

Abstract: Due to the biphasic viscoelastic nature of cartilage, joint loading may result in deformations that require times on the order of hours to fully recover. Thus, cartilaginous tissues may exhibit cumulative strain over the course of each day. The goal of this study was to assess the magnitude and spatial distribution of strain in the articular cartilage of the knee with daily activity. Magnetic resonance (MR) images of ten asymptomatic subjects (six males, four females) with mean age of 29 years were obtained at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
163
6
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 121 publications
(180 citation statements)
references
References 65 publications
(83 reference statements)
10
163
6
1
Order By: Relevance
“…A possible explanation could be the fact that UKA implantation replaces the native articular surface (cartilage five to 12 MPa) with a polyethylene insert (850 MPa) on a metallic femoral component (97 GPa). Cartilage can be compressed under pressure [13,14], while implants less so, which may add to a more inferior position of the tibia. Overstuffing via a thicker polyethylene will increase this effect.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation could be the fact that UKA implantation replaces the native articular surface (cartilage five to 12 MPa) with a polyethylene insert (850 MPa) on a metallic femoral component (97 GPa). Cartilage can be compressed under pressure [13,14], while implants less so, which may add to a more inferior position of the tibia. Overstuffing via a thicker polyethylene will increase this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Next, the MR images were imported into solid modeling software (Rhinoceros, Robert McNeel and Associates, Seattle, WA) so that outlines of the bony cortices and articular cartilage surfaces could be traced. These line models were converted into point clouds and 3D meshes of the femur, tibia, and articular cartilage were created with Geomagic Studio software (3D Systems, Rock Hill, SC) (Figure 1) (Coleman et al, 2013). This method has been previously validated for measuring tibiofemoral cartilage thickness (Van de Velde et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…This method has been previously validated for measuring tibiofemoral cartilage thickness (Van de Velde et al, 2009). Additionally, a recent study from our laboratory demonstrated a coefficient of repeatability of 0.03 mm in measuring tibial, femoral, and patellar cartilage thickness (Coleman et al, 2013), corresponding to a difference in cartilage thickness of 1% (Coleman et al, 2013; Widmyer et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…The proteoglycan content of the PCM is generally higher than that of the surrounding ECM. Therefore, tissue deformation and the associated changes in interstitial water content that occur during loading (Coleman et al, 2013) will result in dynamic changes in the physicochemical and osmotic environment of the chondrocyte (Haider et al, 2006). Importantly, a growing body of evidence suggests that osmotic changes may provide critical signals for regulating the chondrocyte response to loading (Chao et al, 2006; O'Conor et al, 2014).…”
Section: Introductionmentioning
confidence: 99%